2002
DOI: 10.1074/jbc.m204171200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation, Complementation, and Heterologous Expression ofencP, a Novel Bacterial Phenylalanine Ammonia-Lyase Gene

Abstract: The enzyme phenylalanine ammonia-lyase, which catalyzes the nonoxidative deamination of L-phenylalanine to trans-cinnamic acid, is ubiquitously distributed in plants. We now report its characterization for the first time in a bacterium. The phenylalanine ammonia-lyase homologous gene encP from the "Streptomyces maritimus" enterocin biosynthetic gene cluster was functionally characterized and shown to encode the first enzyme in the pathway to the enterocin polyketide synthase starter unit benzoyl-coenzyme A. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 22 publications
4
75
0
Order By: Relevance
“…DNA fragments containing the targeted genes were PCR amplified (Table 2), cloned into the E. coli-streptomycete conjugal transfer vector pKC1139, and conjugated into "S. maritimus" as previously described for the construction of the related encP mutant "S. maritimus" KP (20). The singlecrossover mutants were selected after propagating transconjugants on SGGP (21) plates at 37°C, and apramycin-resistant colonies were confirmed by Southern hybridization with biotinylated gene probes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA fragments containing the targeted genes were PCR amplified (Table 2), cloned into the E. coli-streptomycete conjugal transfer vector pKC1139, and conjugated into "S. maritimus" as previously described for the construction of the related encP mutant "S. maritimus" KP (20). The singlecrossover mutants were selected after propagating transconjugants on SGGP (21) plates at 37°C, and apramycin-resistant colonies were confirmed by Southern hybridization with biotinylated gene probes.…”
Section: Methodsmentioning
confidence: 99%
“…These genes are arranged on four transcripts neighboring the enterocin polyketide synthase (PKS) genes encA, encB, and encC. We previously characterized the unique phenylalanine ammonia-lyase (PAL; EC 4.3.1.5) gene encP and showed that its inactivation resulted in the abolishment of de novo cinnamic acid and enterocin synthesis (20). Enterocin biosynthesis could be restored in the encP-inactivated mutant "S. maritimus" KP through supplementation with cinnamic or benzoic acid as well as complementation with plasmid-borne encP.…”
mentioning
confidence: 99%
“…Recently, a bacterial PAL was detected in Streptomyces maritimus, which uses the produced trans-cinnamic acid as a precursor for the antibiotic enterocin (Xiang and Moore, 2002). Again, sequence alignments revealed that the characteristic insertions were missing, indicating a closer relationship to HAL than to the plant and fungi PAL.…”
Section: The Pal and Hal Superfamilymentioning
confidence: 99%
“…The only case in which prokaryotic PAL activity has been clearly correlated to a biosynthetic protein is EncP from S. maritimus, which is needed for enterocin biosynthesis (Xiang and Moore, 2002). Although this enzyme shows higher similarities in size and sequence to prokaryotic HALs than to plant PALs (which is also the case for the above mentioned gene in S. aurantiaca), Phe was unambiguously proven as the substrate of EncP by heterologous expression of encP and production of cinammic acid in Streptomyces coelicolor.…”
Section: Phe Ammonium Lyase (Pal) the First Dedicated Secondary Metamentioning
confidence: 99%